2016
DOI: 10.1016/j.lingua.2016.03.005
|View full text |Cite|
|
Sign up to set email alerts
|

Disentangling sources of difficulty associated with the acquisition of accusative clitics in French

Abstract: Accusative clitic pronouns are acquired later than both nominative and reflexive pronouns in typically developing French-speaking children. However recent research suggests that not all these clitics are equally difficult, 3rd person accusative clitics (ACC3) being more problematic than 1st and 2nd person. In this study, we explored three properties which could make ACC3 complex: (1) gender marking, (2) discourse-participant independent reference, and (3) optionality in spoken French. We have created specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…According to phonological-prosodic accounts, 3DO clitics are omitted since they are functional elements realized by monosyllabic weak morphemes with short duration that are not prone to straightforward grammaticalization [Leonard's surface Hypothesis-(Leonard, 1998) and subsequent research inspired by the hypothesis]; according to Wexler's maturational account (Wexler, 1998(Wexler, , 2003; and subsequent research adopting this hypothesis), young children only achieve one agreement operation on a constituent, and 3DO clitics are omitted in Italian because they are involved in more than one syntactic agreement operation in this language. More recent research argued that the processing, the storing and the retrieval of gender and person features associated to 3DO is challenging for children [see discussion and references in Delage et al (2016)]. In our study, we will argue that these explanations are problematic and that problems in 3DO clitics production depend on challenging syntactic operations of 3DO clitic derivation.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…According to phonological-prosodic accounts, 3DO clitics are omitted since they are functional elements realized by monosyllabic weak morphemes with short duration that are not prone to straightforward grammaticalization [Leonard's surface Hypothesis-(Leonard, 1998) and subsequent research inspired by the hypothesis]; according to Wexler's maturational account (Wexler, 1998(Wexler, , 2003; and subsequent research adopting this hypothesis), young children only achieve one agreement operation on a constituent, and 3DO clitics are omitted in Italian because they are involved in more than one syntactic agreement operation in this language. More recent research argued that the processing, the storing and the retrieval of gender and person features associated to 3DO is challenging for children [see discussion and references in Delage et al (2016)]. In our study, we will argue that these explanations are problematic and that problems in 3DO clitics production depend on challenging syntactic operations of 3DO clitic derivation.…”
Section: Introductionmentioning
confidence: 75%
“…These properties mainly characterize 3DO clitic pronouns in Italian. In what follows, we will concentrate on third person clitic pronouns because they have been the focus of extensive acquisition research which has yielded some interesting findings; for instance, a number of studies have shown that the production and comprehension of first and second person direct object clitics is relatively unproblematic, while third person clitics are challenging [see Delage et al (2016) for an extensive discussion e references found there]. In the next sections, we will sketch the main features of the syntactic theories accounting for Italian 3DO clitics and we will discuss some acquisition data in both typical and atypical language development.…”
Section: Italian 3do Clitics: Their Features Their Acquisition Theimentioning
confidence: 99%
“…In a context of language contact, SNs, despite being native speakers, may also experience some degree of variation when extracting, processing and integrating the syntactic, semantic and specific morphological information of a word with its concept that affects the mapping of gender features onto clitics. As mentioned in the introduction, evidence for this difficulty with third person clitics has also be found in French L1 monolingual acquisition (Delage et al 2016).…”
Section: Discussionmentioning
confidence: 67%
“…Difficulties in the L2 acquisition of gender features affects not only nouns but also pronominal forms. In the case of accusative clitics, in addition to evidence of difficulties in the acquisition of gender among L2 learners (Grüter 2005;Mayer and Sánchez 2016), there is evidence from child monolingual acquisition of French that clitics marked for gender (third person) are more difficult to acquire than those not marked for it (first and second person) (Delage et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the original task, eight items also elicit 1REF (and 1NOM) clitics, entailing a configuration in which the person of the two clitics of the cluster agree in person (je me ''I myself''), and eight items elicit 1ACC clitics, in a configuration in which there is number mismatch (il/elle me ''he/she me''). As Delage et al (2016) have shown (see also Haiden, 2011), morphological features of the clitic cluster influence performance even in TD children, with mismatch increasing the complexity of the required calculation. The original task includes the simpler configurations alongside the more complex ones, whereas Durrlemann and Delage's task includes only the more complex ones.…”
Section: Discussionmentioning
confidence: 96%